The panel of linked administrative data of CERS databank - Anna Sebők (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2019)
The Databank of the Centre for Economic and Regional Studies has established Admin3, the third round of the Panel of Administrative Data. The data source contains administrative data of the National Health Insurance Fund Administration, the Hungarian State Treasury, the National Tax and Customs Administration, the Ministry of Finance and the Educational Authority on a sample of 50% of the Hungarian population between 2003 and 2017. Based on these data an individual-and firm-level, anonymized panel dataset will be created which contains monthly individual observations on educational activity, employment status, occupation, gross wages, health events etc.
Keywords: C8; C80; C81; C82; C89; 330; Register data; data integration; labor market data; health data; educational data; National Assessment of Basic Competencies data